Does Procrastination Always Predict Lower Life Satisfaction? A Study on the Moderation Effect of Self-Regulation in China and the United Kingdom - Yang, Zeyang (Frontiers in Psychology, 2021)
Aims: Studies have shown the predictive effects of procrastination and self-regulation on wellbeing. However, little is known about the interactive effect between procrastination and self-regulation. This study explores whether self-regulation moderates the link between procrastination and wellbeing among British and Chinese young adults. Methods: This study adopted self-reported questionnaire survey among two hundred and sixty-five British and four hundred and seventy-five Chinese participants. SPSS and AMOS were used to test the moderation effect. Multi-group path analysis was used to compare the two countries. Results: Data analysis shows that self-regulation was a significant moderator of the relationship between procrastination and life satisfaction in the Chinese sample but not in the British sample. Procrastination predicted low life satisfaction only among the Chinese students with low self-regulation. Discussion: This study indicates that the effects of procrastination on wellbeing could be changed at different levels of self-regulation. Cultural difference can be an important factor when investigating procrastination and its impacts.